The relationship of anxiety, nutritional status and independence with quality of life of hypertension elderly in the work area of Bukit Hindu Puskesmas, Palangka Raya City - Ni Luh Putu Dewi Novilasari; Nia Kania; Roselina Panghiyangani; Muhammad Abdan Sadiqi; Syamsul Arifin (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This research aimed to examine the relationship between anxiety, nutritional status, independence, and Quality of Life (QoL) among the elderly with hypertension treated at the Bukit Hindu Public Health Center in Palangka Raya City. Methodology: This research was a cross-sectional study conducted in the waiting clinic area of the Bukit Hindu Public Health Center in Palangka Raya City. Forty participants were randomly selected for this survey. The chi square test and multiple logistic regression analyses were used to examine the data. Findings: Physical, psychological, social, and environmental domains show no significant relationship between anxiety and QoL in the hypertensive elderly. However, the nu tritional status variable does show a significant relationship between QoL and the hypertensive elderly. When looking at the relationship’s physical, psychological, social, and environmental aspects, the elderly with hypertension who receive care at the Bukit Hindu Public Health Center in Palangka Raya City have a higher QoL when they are more independence-sufficient. To a greater extent than any other factor, the independent variable influences the physical, mental, and social dimensions of older people’s QoL due to hypertension. In contrast, nutritional status is a significant determinant of quality of life (QoL) for the elderly with hypertension in the environmental domain. Implications/Novel Contribution: The findings from this study will contribute knowledge and provide valuable information for future researchers.